Damaging flood risk in the Portuguese municipalities - Santos, Pedro Pinto (2020)
Riverine floods are responsible for significant human and material losses. Climate change scenarios pose additional challenges to flood susceptibility and risk assessment (Kundzewicz et al., 2014; Winsemius et al., 2015). While in recent decades the increases in global flood damage have mainly been driven by population and economic activity growth in flood-prone areas, climate change projections launch a high level of uncertainty about future impacts, showing, however, that flood protection standards can play a relevant part in mitigating such effects (Winsemius et al., 2015) [...]